Mifepristone Ameliorates Sleep Deprivation - Induced Oxidative Stress in the Testis of Rats (African Journal of Biomedical Research, 2020)
Sleep deprivation is becoming an everyday experience and has been associated with generation of chronic stress and low level of testosterone. This study aimed to evaluate the influence of mifepristone on testicular oxidative stress and serum inflammatory markers in sleep deprivation induced chronic stress in rats. Twenty five rats were divided into five groups (n=5) and designated as follows: Group 1: Control, Group 2: sleep deprived (SD), Group 3: sleep deprived and sleep recovery (SD+SR), Group 4: sleep deprived mifepristone treated (SD+MIF), Group 5: sleep deprived and recovery mifepristone treated (SD+SR+MIF). Rats were sleep deprived for five days, mifepristone 10mg/kg was given orally for mifepristone treated groups while recovery groups were allowed to recover for five days. At the end of the experiment, cortisol, testosterone, interleukin 6 (IL-6) and c reactive protein (CRP) were analysed while testicular malondialdehyde (MDA), catalase (CAT), and glutathione (GSH) were also evaluated. Rats in SD group had significantly increased level of MDA and cortisol, IL-6 and CRP levels (p